Contexto Laboral De Las Personas Con Discapacidad De La Ciudad De Loja - Cuenca Collaguazo, Rosa Elizabeth (2016)
Disability is defined as the externalization of functional impairments, physical, mental and sensory limitations that relate to the social context produce handicaps or disabilities. These express the gap between the capabilities and potential of the disabled person and environmental demands. This thesis is part of a study conducted in the city of Loja people with disabilities has been achieved inserting the workplace through the Ministry of Labour Relations - Regional Directorate Loja, seeks to understand the various problems being experienced in their jobs and the location according to your profession and relationships with colleagues. It details a complete analysis of law enforcement, the motivation that this group to apply for a job, in this investigation the following objectives: "To promote the employment of persons with disabilities to ensure their right to work " " theoretically sustain the problems of people with disabilities and their status in the workplace " and" Determining the causes and effects of labor market exclusion for people with disabilities by their level of education” The methods used were the scientific method, deductive method , analytical method , descriptive statistical method, such as observation techniques and the survey was also raised as a support tool that was applied to the operated population , for the collection of information, same as allowed us to know in depth the problem under study . According to the results of the investigation; most prevalent disability is physical, mental and visual respectively. It also demonstrates a high rate of people with disabilities who are excluded in the workplace primarily by their level of education as most have only primary education, due to the following factors incidents such as the geographical areas in which they live , the lack of accesses as the permanent support of a family to move to the educational institution is required this situation occurs in all forms of disability; and tools such as the range in people with visual disabilities to use numbers also rule to write in Braille , also tiflotécnicos artifacts such as calculator, clock , telephone and most importantly are needed a computer system adapted to the jaws and the Braille printer ; considering that the acquisition of these tools implies an economic cost. Partially known protection laws, job stability is at least 1 to 2 years, also claim that it is not easy to get a job and have not been supported by any institution professionalized. This environment has not allowed access to higher positions in public and private institutions and proceeded to fill positions as public servants support charges: auxiliary file, scanning documents, file management Unit and Talent overall income documentation file and call center. For their part, business managers state that disabled people they work with need to professionalize easier and suitable for their employment not be dependent on a single job position , recognize that not everyone could achieve academically and therefore only may offer positions as cashiers , customer service and office assistants jobs in which required observation always be superior .